Serine Proteinases Secreted by Two Isolates of the Fungus Alternaria solani - Tatiana A. Valueva; Natalia N. Kudryavtseva; Ekaterina L. Gvozdeva; Alexis V. Sof’in; Natalia Yu. Il’ina; Marina A. Pobedinskaya; Sergei N. Elansky (Journal of Basic & Applied Sciences, 2013)
It is well-known Alternaria solani Sorauer is the causative agent of alternariosis. In this paper, serine proteinases secretion by two genetically related isolates of the fungus, collected from potato and tomato plants grown in central Russia have been studied. The data clarify functions of these enzymes in the process of pathogenesis in which they can play a pivotal role. Also, the data should allow classifying Alternaria’s strains more precisely. It was found that the two isolates produced trypsin-like and subtilisin-like proteinases during growth both in synthetic culture medium and in medium containing heat-stable vegetable proteins. There were significant differences in the influence of the environment on the serine proteinase secretion by the potato and tomato isolates of A. solani. The proportion of such serine proteinases as trypsin-like and subtilisin-like enzymes depends on the composition of the growth medium, especially on the available organic nitrogen form, as well as features both of the pathogenic fungus and of the host plant. So, the tomato isolate demonstrated weak growth and low level or absence of serine proteinase excretion on cultivation with the medium containing proteins extracted from potato tubers and pea seeds. The potato isolate secreted many more serine proteinases, among which the trypsin-like enzymes dominated. Our data suggest that the tomato isolate, when grown on medium with proteins extracted from potato tubers, lost pathogenicity and became to behave as a saprophyte, while the potato isolate retained its pathogenic properties on growth on any tested medium.